Peningkatan Pengetahuan Swamedikasi untuk Anak “Bunda Kenal Obat, Anak Sehat” - Muslim, Ahmad Suriyadi; Rahmawati, Riana Putri; Kurniawati, Pratiwi; Malihatin, Putri Dewi; Setianingsih, Indah Wahyu (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2025)
A child can be defined as a human being under the age of 18, including an unborn child. All aspects of a child's needs are heavily dependent on their parents, particularly their mother. This includes basic needs such as nutrition, affection during growth and development stages, and guidance on parenting, all of which are primarily provided by the mother. During the growth and development stages, children are vulnerable to various illnesses, including fever, cough, cold, diarrhea, itchiness, and rashes. As a result, mothers need to be able to provide self-medication or swamedikasi. This community service program aims to enhance the knowledge and understanding of mothers, specifically those of KB Aisyiah 1 Kudus, in providing self-medication for their children. The program consists of several stages, including obtaining permits, distributing pre-test questionnaires, presenting materials, and concluding with post-test questionnaires. The program's evaluation is based on the analysis of the pre-test and post-test questionnaires. The community service program lasted for approximately four days, with participants comprising mothers of KB Aisyiah 1 Kudus students. The prevalence of participants' ages ranged from 25-30 years, with most having more than one child and being housewives (seven participants). The program resulted in a significant increase in the average pre-test and post-test scores, with a 57.14% improvement. This indicates that the program has successfully enhanced the mothers' knowledge and understanding of self-medication.